Lived Precarity: Paradoxes of Human Security among Undocumented Indonesian Migrant Workers in Malaysia - Novalita Radiatie; Winda Nurlaily Rafikalia Iskandar; Apriadi Apriadi; Rafiq Adi Wardana (Universitas Darul Ulum, 2026)
This paper examines the vulnerability of undocumented Indonesian migrant workers in Malaysia by highlighting the human security paradox within the migration regime. Undocumented status is not only an administrative condition but also a structural mechanism that produces systemic illegality, insecurity, and uncertainty. Drawing on Nicholas De Genova’s argument that migrant illegality is socio-politically produced through state regulation, the paper argues that the logic of protection within the migration regime not only fails to reduce vulnerability but rather perpetuates it in everyday life. This paradox illustrates how the existing protection regime, rather than mitigating vulnerability, contributes to its persistence among undocumented migrant workers. Using qualitative methods and a case study approach, this research explores the lived experiences of undocumented migrant workers through in-depth interviews, participant observation, and secondary sources. The findings indicate that fear of detention and deportation constrains undocumented workers from accessing formal protection channels and compels them to rely on informal networks of solidarity. This dynamic demonstrates that illegality restricts access to rights and protections, thereby reproducing the vulnerabilities that protection frameworks are intended to address. By situating the experiences of undocumented migrant workers within a broader security framework, this research contributes to critical migration and human security studies.